PENGARUH SISTEM PENGENDALIAN INTERN, ASIMETRI INFORMASI, KESESUAIAN KOMPENSASI DAN MORALITAS MANAJEMEN TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI (Studi Empiris pada Rumah Sakit Islam Ibnu Sina Sumatra Barat) - Rifqi Abdillah A; Nur Azlina; Adhitya Agri Putra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aimed to obtain empirical evidence about the influence of internal control system, information asymetry, suitability compensation and Management Morality to the tendency of accounting fraud. This study used primer data with quitonaiers. The population of this study was obtained from a sample of all Islamic hospital Ibnu Sina of Western Sumatra. The sample was determined using the saturated samples with unit of analysis of this study is a director of the hospital, the head of the public department, the head of human resource, the chief financial officer, the head of the pharmaceutical unit, internal auditor and the accounting staff, with a totals 102 respondent, so the questionnaire is returned as many 84 pieces. The analysis technique used multiple linear regression analysis using SPSS ver. 25 computer program. The result of the study showed that (1) partially the internal control affected the accounting fraud, (2) partially the informational asymmetrical affected the accounting fraud, (3) partially the compliance compensation affected to the accounting fraud, (4) partially the management morality affected to the accounting fraud.Keyword : fraud, internal, asymetry, compensation and morality